The impact on disaster governance of the intersection of environmental hazards, border conflict and disaster responses in Ladakh, India. (October 2018) - Field, Jessica; Kelman, Ilan
Abstract: The Indian border region of Ladakh, in Jammu and Kashmir State, has a sensitive Himalayan ecosystem and has experienced natural hazards and disasters of varying scales over the decades. Ladakh is also situated on a fault-line of multiple tensions, including ongoing border disagreements and intermittent conflict with China and Pakistan. The Indian army has thus become a permanent fixture in the region. This paper examines the implications of the intersection of these environmental and security factors for disaster governance in the region. Using Social Domains theory, the paper argues first, that a hazard-centred paradigm of 'universal' disaster science emerges from the colonial period, which has continued to dominate disaster management in the region today. Secondly, it argues that, as the border military complex expanded significantly in Ladakh from independence in 1947 and the region faced a number of conflicts, disaster governance has been additionally shaped by national security priorities. The paper then examines the impacts of that hazard-centred, military-led disaster governance for the population of Ladakh. These include: a relief-orientated disaster management approach, reduced civil society presence and capacity in the region, and limited local ownership of disaster risk reduction activities. This case study provides important insight into why disaster risk reduction has been slow or absent in conflict zones.